Implementasi Group Investigation Dengan Pendekatan Problem Based Learning untuk Meningkatkan Kemampuan Hasil Belajar Mahasiswa - Efa Wahyu Prastyaningtyas; Hestin Sri Widiawati (International Consortium of Education and Culture Research Studies, 2018)
The learning approach used by a lecturer should be able to keep up with the times (innovative). Accounting system is a course that must be taken by students of economic education. Achievement of learning to be achieved in this course is students are able to analyze, compile and design the accounting system at the company. Based on the results of interviews and observations made during the learning process took place, obtained the results are still many students who do not pay attention to the explanation of the lecturer. This resulted in low learning outcomes, with 55% showing that 35 students did not meet the Minimum Exhaustiveness Criteria (KKM). In this study used approach to learning that refers to the approach of group investigation and problem-based learning with the aim of improving the ability of students to analyze and provide student solutions in the process of learning accounting system so as to improve learning outcomes. This study uses a classroom action research type. The data analysis of this research is descriptive quantitative. The result of the research shows that the approach of study which refers to group investigation and problem based learning approach can improve student learning outcomes from cycle 1 to cycle II in the problem orientation stage until the presentation of the final result.